A study on obstetric patients with corona virus infection requiring critical care - Preet, Adarsh; Palve, Tushar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Coronavirus cause respiratory tract infection that can range from mild to lethal like cold, fever, cough, shortness of breath, fatigue, chills, body aches, headache, sore throat, loss of smell or taste, nausea, diarrhoea, pneumonia, respiratory failure, septic shock and death. The purpose of this study was to describe the clinical manifestations of obstetric patients with COVID-19 infection requiring critical care, their 02 requirements, complications, co-morbidities associated and mortality related to it. Methods: A study was conducted in the Department of Obstetrics and Gynecology, Cama and Albless hospital, Mumbai including 31 patients with SARS CoV-2 infection requiring critical care. Necessary information such as their detailed clinical, and obstetric history, clinical examination, investigations was noted. Results: In our study, the most common symptoms were shortness of breath, followed by fever. PIH was the most common co morbidity associated and pneumonia as most common complication. Anemia, thrombocytopenia and NLR>4 were found more common in intensive care unit (ICU) admitted patients as compared to non-ICU admitted patients. 77.4% of patients had abnormal chest X-ray with 25.8% requiring mechanical ventilation. Conclusions: COVID 19 infection is affecting pregnant women resulting in mild to lethal disease. Most of pregnant women are asymptomatic or have mild disease but some of them require critical care. These women should be monitored carefully to prevent maternal morbidity and mortality.